1999
DOI: 10.1007/s005340050119
|View full text |Cite
|
Sign up to set email alerts
|

Mucin-producing tumors of the pancreas: clinicopathological features, surgical treatment, and outcome

Abstract: Mucin-producing tumors (MPTs) of the pancreas are increasingly being recognized. To evaluate the appropriate surgical treatment and predict the prognosis of MPTs, we performed a retrospective clinicopathological study in 51 patients, 27 with benign tumors and 24 with borderline/malignant tumors. Three of the malignant tumors showed stromal invasion and lymph node metastasis on histological examination. Of the 24 patients with borderline/malignant tumors, 2 died of MPTs and 4 died of other diseases. At the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…It is important to distinguish the colloid from the tubular/ductal types of invasive carcinoma because patients with the former have a better prognosis than patients with the latter (see below) (51). IPMNs may be associated with extrapancreatic malignancies (61)(62)(63). Twelve of 79 patients with an IPMN reported by Kamisawa et al had a synchronous or a metachronous gastric cancer, and 7 had colon cancer (62).…”
Section: Pathologic and Molecular Featuresmentioning
confidence: 99%
“…It is important to distinguish the colloid from the tubular/ductal types of invasive carcinoma because patients with the former have a better prognosis than patients with the latter (see below) (51). IPMNs may be associated with extrapancreatic malignancies (61)(62)(63). Twelve of 79 patients with an IPMN reported by Kamisawa et al had a synchronous or a metachronous gastric cancer, and 7 had colon cancer (62).…”
Section: Pathologic and Molecular Featuresmentioning
confidence: 99%
“…The treatment of choice for tumors of the head of the pancreas, the typical location of IPMT [40], is radical pancreatoduodenectomy based on the specifications of an international workshop on surgical procedures in 1998 [37,41,42]. Whether it should be performed as a pylorus-preserving procedure or as the classical KauschWhipple operation is still debated.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In their study, K-ras mutations were found in adenomas in 62% of patients with IPMNs, 65% of whom had multiple, distinct mutations in different lesions. These results provide molecular evidence for field cancerization in pancreases bearing IPMNs and suggest that patients with IPMN are at risk for synchronous and/or metachronous multiple tumors before and after surgery [36,55,56].…”
Section: Field Cancerization In Pancreases With Ipmnsmentioning
confidence: 94%
“…An important clinicopathologic feature of IPMN is that multifocal occurrence of IPMN has been observed in the same pancreas [12,16,55,56]. The incidence of tumor multifocality of IPMN ranges from 9.8 to 32% [12,16,55,56], and recurrences after surgical resection have been reported [16,55,56].…”
Section: Multifocal Occurrence Of Ipmnmentioning
confidence: 96%
See 1 more Smart Citation